Oviposition and development of two plantain pests, Scopula rubraria and Epyaxa rosearia (Lepidoptera: geometridae). Issue 4 (2nd October 2018) - Gerard, Philippa J.; Philip, Bruce A.; Ferguson, Colin M.; Eden, Tina M.
ABSTRACT: Two native geometrid moths, Scopula rubraria and Epyaxa rosearia, have emerged as major pests of narrow-leaved plantain, a forage plant that has grown in popularity in summer-dry regions of New Zealand. With little known about these two moth species, laboratory studies were undertaken to gain greater understanding of their oviposition and development. Both species have a strong preference for ovipositing on hairy rather than smooth foliage, and are therefore likely to target young leaves. S. rubraria has five instars, while E. rosearia has five or six, with the latter more prevalent at 18°C and below. S. rubraria has a higher temperature threshold of 13.3°C for egg hatch and a lower degree day requirement of 459 to complete development, compared with 6.3°C and 1117, respectively, for E. rosearia . The results suggest both species would start hatching in mid-spring and have three generations by mid-autumn.